Empowering Ulos Artisans through Financial Literacy and Digital Marketing: A Sustainable Approach to Preserving Cultural Heritage in Sipirok, Indonesia: English - Siregar, Narumondang Bulan; Nasution, Abdillah Arif; Herubawa, Dio Agung; Azhar, Ibnu Austrindanney Sina (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
The ulos weaving business in Padang Bujur Village, Sipirok District, North Sumatra, plays a vital role in preserving cultural heritage and supporting the local economy. However, these enterprises face significant challenges, including inadequate financial management skills and limited digital marketing adoption. These issues were exacerbated during the COVID-19 pandemic, which disrupted traditional sales channels and reduced market demand. This program documents a community service program aimed at addressing these challenges through two key interventions: basic accounting training and the adoption of digital marketing strategies. The program provided artisans with practical knowledge in financial management, including transaction recording, cash flow management, and simple financial reporting. Furthermore, digital marketing solutions such as the creation of blogs, utilization of social media platforms, and optimization of e-commerce tools were introduced to expand market reach and improve product visibility. The results demonstrated a significant improvement in artisans' financial literacy and their ability to manage business finances transparently and effectively. Additionally, the implementation of digital marketing strategies increased customer engagement and broadened the market for ulos products, including access to national and international buyers. This program highlights the importance of integrating traditional craftsmanship with modern business practices to sustain micro-enterprises in the digital era. Future efforts should focus on advanced training and fostering partnerships with stakeholders to ensure long-term sustainability and growth.